The Research Value of Biphasic Registration Quantitative Computed Tomography Emphysema Index in the Evaluation of Mild to Moderate COPD - Xionghui WANG; Juan PAN; Yuan NIU; Min SHEN; Weiling YIN; Jianlong LI; Xiaoqi HUANG; Youmin GUO (CT Lilun yu yingyong yanjiu, 2024)
Objective: To find the optimal quantitative index of emphysema by comparing and analyzing the quantitative indexes of emphysema in patients with mild to moderate chronic obstruction pulmonary disease (COPD) via registered biphasic quantitative computed tomography (QCT). Methods: We retrospectively collected 55 healthy controls, 21 Global Initiative for Chronic Obstructive Pulmonary Disease (GOLD) 1 case, and 31 GOLD 2 cases in our hospital. We imported the CT raw DICOM data into the "Digital Lung" analysis platform and measured the LAA-950% at the end of deep inspiration and the LAA-910% at the end of deep expiration. The expiratory and inspiratory CT images were registered. Then, the percentage of emphysema area (PRMEmph%), the percentage of functional small airway disease area (PRMfSAD%), and the percentage of the normal area (PRMNormal%) were calculated according to the threshold method. Pulmonary function indicators included FVC, FEV1%, and FEV1/FVC. Differences in general data, CT quantitative indexes, and pulmonary function between groups were assessed using the independent sample t-test, Mann–Whitney U test, or chi-square test, and the correlation was analyzed using Spearman correlation. The receiver operating characteristic (ROC) curve was drawn to analyze the diagnostic performance of CT quantitative parameters for emphysema in patients with mild to moderate COPD. Results: There were significant differences in sex, smoking index, FEV1%, FEV1/FVC, inspiratory phase LAA%-950, expiratory phase LAA%-910, PRMEmph%, PRMfSAD%, and PRMNormal% between the mild to moderate COPD patients and normal control groups. The inspiratory phase LAA%-950 was negatively correlated with FEV1/FVC, the expiratory phase LAA%-910 and PRMEmph% were negatively correlated with FVC, FEV1%, and FEV1/FVC. ROC curve analysis results showed that the areas under the curve of inspiration phase LAA%-950, expiratory phase LAA%-910, and PRMEmph% were 0.742, 0.861, and 0.876, respectively. Among them, the area under the curve of the PRMEmph% index was the largest, with a corresponding critical value of 9.84%, a sensitivity of 76.90%, and a specificity of 94.50%. Conclusion: Quantitative CT emphysema index LAA%-950 in the inspiratory phase, LAA%-910 in the expiratory phase, and PRMEmph% in biphasic can objectively evaluate emphysema in patients with mild to moderate COPD, among which PRMEmph% is the best evaluation index.